Rancang bangun dan analisa trial and eror prosthethic servo power handa - Yanalseta, Rifaldi; Suryadi, Dedi; Saputra, Roni Permana (UNIB Press, 2025)
Prosthetic hands are designed to help people with disabilities work. This research aims to make a prosthetic hand using a 3D printing machine with a focus on using Solidworks software for model design, Ultimaker Cura software for slicing printing in the form of G-Code, and filler material in the form of PLA filament. The main components used involve a servo motor (MG996), Arduino Uno, and breadboard. This research focuses on making designs using solidworks, using servo motors (MG996), and using PLA filament material. The data collection process is divided into three stages: design creation, G-code creation, and printing, as well as the data collection process which involves trial and error on the prosthetic hand. The results of this research show that although in general all the fingers of the prosthetic hand can move, there are some fingers that experience problems following program commands. Factors such as design, manufacturing defects, hinges, and connecting straps between the servo motor and the finger affect the movement of the prosthetic hand's fingers. Although some fingers can move well, there are also those who experience difficulty in movement.